2011
DOI: 10.1007/s13312-011-0043-8
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal zinc supplementation for prevention of mortality and morbidity in breastfed low birth weight infants: Systematic review of randomized controlled trials

Abstract: In view of no convincing evidence of benefits from the limited data available, currently there is no justification for recommending routine zinc supplementation for breastfed LBW newborns in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The dietary recommendations for preterm neonates suggest 1.1-2 mg $ kg Zn 21 $ d 21 (29). We used higher zinc doses; the use of zinc doses above the dietary guidance level is an emerging research area in pediatric nutrition (10,16). Many studies suggest that 10-20 mg Zn/d is able to limit the risk of infections in children (40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The dietary recommendations for preterm neonates suggest 1.1-2 mg $ kg Zn 21 $ d 21 (29). We used higher zinc doses; the use of zinc doses above the dietary guidance level is an emerging research area in pediatric nutrition (10,16). Many studies suggest that 10-20 mg Zn/d is able to limit the risk of infections in children (40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Total zinc intake in the zinc group ranged from 9.7 to 10.7 mg/d. High doses in preterm neonates seem justified because of the lower stores at birth, the higher requirements for growth, and potentially other stress factors present during prematurity (16). In a large trial, Sazawal et al (15) showed a reduction in mortality in the first 9 mo of life in an RCT that enrolled full-term small-for-gestational-age infants who received oral zinc supplementation at high doses (5 mg/d).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have evaluated the role of zinc in neonatal and early infancy periods in LBW infants. The two large community trials among these infants [19,20], a meta-analysis of whose results [21] does not suggest benefit of zinc supplementation to LBW infants, had enrolled mostly term LBW infants with a mean birth weight of more than 2,000 g. On the other hand, studies in infants with a lower birth weight (<2,000 g) suggest that there is a positive effect of zinc supplementation on growth [22,23,24,25] and motor development of these infants [25]. Also, one large community-based trial on zinc supplementation in children aged 1–35 months in Nepal reports a 44% reduction in mortality among the subgroup of infants less than 2,000 g (RR 0.56; 95% CI 0.3–1.04) [26].…”
Section: Discussionmentioning
confidence: 99%
“…A large and rapidly growing literature has explored the degree to which zinc supplementation can improve population health in general, and child health in particular [610]. While some studies have documented negative effects of zinc supplementation on iron absorption [11], the adverse effects of zinc supplementation on concentrations of hemoglobin, serum ferritin, and serum copper appear limited [1215].…”
Section: Introductionmentioning
confidence: 99%